Droid tales, episodes I-III - Howard, Kate; Price, Michael (Screenplay writer) (New York : Scholastic Inc., 2016)
The legendary conflict between the Jedi and the Sith is retold through the eyes of C-3PO annd R2D2! When Obi-Wan and Qui-Gon Jinn meet young Anakin Skywalker, little do they know that their actions will determine the fate of the entire galaxy.
4.2
3-6
Keywords: Star Wars fiction; Androids -- Fiction; Space warfare -- Fiction; Life on other planets -- Fiction; LEGO toys -- Fiction; Star Wars fiction; Science fiction